Wild Bitter Melon Exerts Anti-Inflammatory Effects by Upregulating Injury-Attenuated CISD2 Expression following Spinal Cord Injury. (30th September 2020) - Kung, Woon-Man; Lin, Chai-Ching; Kuo, Chan-Yen; Juin, Yu-Ching; Wu, Po-Ching; Lin, Muh-Shi
Abstract : Background . Spinal cord injuries (SCIs) induce secondary neuroinflammation through astrocyte reactivation, which adversely affects neuronal survival and eventually causes long-term disability. CDGSH iron sulfur domain 2 (CISD2), which has been reported to be involved in mediating the anti-inflammatory responses, can serve as a target in SCI therapy. Wild bitter melon (WBM; Momordica charantia Linn. var. abbreviata Ser.) contains an anti-inflammatory agent called alpha-eleostearic acid ( α -ESA), a peroxisome proliferator-activated receptor- β (PPAR- β ) ligand. Activated PPAR- β inhibits the nuclear factor κ B (NF- κ B) signaling pathway via the inhibition of I κ B (inhibitor of NF- κ B) degradation. The role of astrocyte deactivation and CISD2 in anti-inflammatory mechanisms of WBM in acute SCIs is unknown. Materials and Methods . A mouse model of SCI was generated via spinal cord hemisection. The SCI mice were administered WBM intraperitoneally (500 mg/kg bodyweight). Lipopolysaccharide- (LPS-) stimulated ALT cells (astrocytes) were used as an in vitro model for studying astrocyte-mediated inflammation post-SCI. The roles of CISD2 and PPAR- β in inflammatory signaling were examined using LPS-stimulated SH-SY5Y cells transfected with si-CISD2 or scramble RNA. Results . WBM mitigated the SCI-induced downregulation of CISD2, PPAR- β, and I κ B and upregulation of glial fibrillary acidic protein (GFAP; marker of astrocyte reactivation) in the spinal cord of SCI mice. Additionally, WBM (1  μ g/mL) mitigated LPS-induced CISD2 downregulation. Furthermore, SH-SY5Y neural cells with CISD2 knockdown exhibited decreased PPAR- β expression and augmented NF- κ B signaling. Conclusion . To the best of our knowledge, this is the first study to report that CISD2 is an upstream modulator of the PPAR- β /NF- κ B proinflammatory signaling pathway in neural cells, and that WBM can mitigate the injury-induced downregulation of CISD2 in SCI mice and LPS-stimulated ALT astrocytes.